7-ketocholesterol inhibits Na,K-ATPase activity by decreasing expression of its Î±1-subunit and membrane fluidity in human endothelial cells - Duran, M. J.; Pierre, S. V.; Lesnik, P.; Pieroni, G.; Bourdeaux, M.; Dignat-Georges, F; Sampol, J.; Maixent, J. M. (Cellular and Molecular Biology, 2010)
As cholesterol, oxysterols, can insert the cell membrane and thereby modify the functions of membrane-bound proteins. The Na,K-ATPase is very sensitive to its lipid environment, seems to be involved in important endothelial functions as the regulation of nitric oxide (NO) release. The effects of 7-ketocholesterol , an oxysterol present in oxidized LDL, was investigated on Na,K-ATPase in isolated human endothelial cells. Cells were incubated 24h with lecithin-, cholesterol- or 7-ketocholesterol liposomes (6 µg/ml). K+-stimulated paranitrophenyl phosphatase activity, reflecting Na,K-ATPase activity, was evaluated as well as cell viability and lipoperoxidation. The expression of Na,K-ATPase subunits mRNAs and membrane fluidity were also investigated. As Na,K-ATPase and nitric oxide seem to be related, we determined the production of NO and the expression of endothelial NO synthase mRNAs. Na,K-ATPase activity was strongly decreased by 7-ketocholesterol. This decrease, not related to lipoperoxidation, was correlated with a decreased expression of the Na,K-ATPase Î±1-subunit messengers and with rigidity of plasma membranes. Cholesterol induced similar effects but was less potent than 7-ketocholesterol. Basal NO production and expression of endothelial NO synthase mRNAs were not modified by 7-ketocholesterol. Our new findings demonstrate that 7-ketocholesterol, used at non toxic doses, was very potent to disrupt the transport of ions by Na,K-ATPase and perturb membrane structure. These data demonstrate that 7-ketocholesterol induces endothelial dysfunction without cell death that may contribute to early events in atherosclerosis.